Optimism and Work Engagement among Bank Professionals - Tantry, Ansarullah; Ali, Zaiba; Ali, Zaiba (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present research was to examine the relationship of optimism and work engagement among bank professionals of State Bank of India, working in Kashmir. A sample of 420 professionals was part of the study, selected by deliberate sampling method. Optimism scale developed, by Seligman (1991), was used to assess levels of optimism and Utrecht Work-Engagement Scale (UWES) (Schaufeli & Bakker, 2004) was used to measure the feelings experiencing in various work situations among the sample of the study. Data was analysed by using Mean, SD, and Perason’s correlation. Findings of this study explained that there is a significantly positive correlation between optimism and work engagement among bank professionals. it can be concluded that optimism plays an important role in enhancing work engagement among bank professionals.